2010
DOI: 10.1016/j.neuroimage.2010.01.061
|View full text |Cite
|
Sign up to set email alerts
|

When does brain aging accelerate? Dangers of quadratic fits in cross-sectional studies

Abstract: Many brain structures show a complex, non-linear pattern of maturation and age-related change. Often, quadratic models (β 0 + β 1 age + β 2 age 2 + ε) are used to describe such relationships. Here, we demonstrate that the fitting of quadratic models is substantially affected by seemingly irrelevant factors, such as the agerange sampled. Hippocampal volume was measured in 434 healthy participants between 8 and 85 years of age, and quadratic models were fit to subsets of the sample with different age-ranges. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
221
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(235 citation statements)
references
References 34 publications
10
221
1
3
Order By: Relevance
“…Poisson model considers varying slops for connectivity changes in both developmental and aging periods. In contrast, the quadratic regression model assumes even slops across both the periods (Fjell et al, 2010), though the quadratic regression model provides a simple way to account for the correlated terms over most of the age range (Allen et al, 2005;Lebel and Beaulieu, 2011). As illustrated in Figure 4, the transcallosal connectivity for different cortical areas changed faster in the developmental period than in the aging period, suggesting that the neural fibers maturate quickly during brain development but degenerate slowly during aging, in good agreement with previous studies (Lebel et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Poisson model considers varying slops for connectivity changes in both developmental and aging periods. In contrast, the quadratic regression model assumes even slops across both the periods (Fjell et al, 2010), though the quadratic regression model provides a simple way to account for the correlated terms over most of the age range (Allen et al, 2005;Lebel and Beaulieu, 2011). As illustrated in Figure 4, the transcallosal connectivity for different cortical areas changed faster in the developmental period than in the aging period, suggesting that the neural fibers maturate quickly during brain development but degenerate slowly during aging, in good agreement with previous studies (Lebel et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…In our results, illustrated in Figure 4.1, the right pallidum did not significantly diminish with age, and the left pallidum displayed a small rate of atrophy. Amygdalae and caudate nuclei also had small rates of atrophy, alongside the hippocampi, though there exists strong evidence the hippocampi follow a nonlinear trajectory at advanced age, and therefore our linear model incurs some bias (FJELL et al, 2010b). The volumetric increase of ventricular structures we reported is consistent with the literature as well (FJELL et al, 2013;WALHOVD et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…These findings have been widely reported in the literature (BAKKOUR et al, 2013;FJELL et al, 2009aFJELL et al, , 2009cFJELL et al, , 2010aFJELL et al, , 2010bFJELL et al, , 2013FJELL et al, , 2014aFJELL et al, , 2014bFJELL et al, , 2015dGOODRO et al, 2012;HARADA;NATELSON LOVE;TRIEBEL, 2013;LEMAITRE et al, 2012;LOCKHART;DECARLI, 2014;MEIER-RUGE et al, 1992;DUCHESNE, 2017a;SALAT et al, 2004;SCAHILL et al, 2003;SOWELL et al, 2007;STORSVE et al, 2014;THAMBISETTY et al, 2010;WALHOVD et al, 2011;WESTLYE et al, 2009;ZHOU et al, 2013;ZIELINSKI et al, 2014). While almost the whole cortex present evidence for age-related thinning, frontal gyri, superior and middle temporal gyri, the temporoparietal junctions and pre-and postcentral gyri display highly consistent thinning across samples, with relative sparing of inferior temporal lobes and anterior cingulate cortices (FJELL et al, 2009a).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…While linear and quadratic regression are often used (e.g., Sowell et al (2003); Hogstrom et al (2013); Madan and Kensinger (2016)), it has been shown that non-linear (spline) regression is more appropriate (Fjell et al 2010;). …”
mentioning
confidence: 99%